Multiphysics Analysis of Ice-Polyurethane Adhesion under Flexural Loading using FEM Analysis - H Eidesen; Z Andleeb; H Khawaja; M Moatamedi (International Journal of Multiphysics, 2021)
This paper presents the Finite Element Analysis (FEA) Multiphysics technique, applied to study the strength of ice adhesion between the surface of polyurethane and ice. The theoretical study of this work is based on the Euler-Bernoulli beam theory that is used to solve a four-point bending problem to give the correlation of displacements with load and longitudinal stresses. The physical samples were prepared by freezing ice over the polyurethane surface and were tested experimentally in a four-point flexural setup. In the experiment, masses were added to the four-point bench until the ice separated from the surface. The results revealed that the ice adhesion on the surface of polyurethane is in the same range as with other polymers. The displacement at the time of separation was recorded, and the same conditions were used to perform numerical simulations in ANSYS® Workbench. The meshed ice-Polyurethane Finite Element Method (FEM) model was tested for sensitivity. A good agreement was found between theoretical, experimental, and numerical simulation results.